2011
DOI: 10.1016/j.foreco.2010.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sugar maple tree growth in relation to the partitioning of elements in xylem along a soil acidity gradient

Abstract: a b s t r a c tPartitioning of elements in tree xylem is being increasingly studied, as it suggests that elements are potentially mobile within the xylem long after their uptake. A recent study revealed that only the most mobile xylem fraction (water-soluble) of base cations (calcium [Ca], magnesium [Mg], and potassium [K]) increased at higher soil acidity, while the two mobile fractions (water-and acid-soluble) of acidic metals-potentially phytotoxic aluminium (Al), cadmium (Cd) and manganese (Mn)-were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 101 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…This shift in values may be attributed to radial translocation through xylem tissue via ray cells that redistributes elements in other portions of wood (Watmough 1999;Bilodeau-Gathier et al 2008). Elements are potentially mobile within the xylem long after their uptake, and the mobility of water-soluble base cations (Ca, Mg, and K) increases at higher soil acidity (Bilodeau-Gauthier et al 2011). McClenahen et al (1989 reported Mn and Ca elements that are likely to move laterally.…”
Section: Discussionmentioning
confidence: 99%
“…This shift in values may be attributed to radial translocation through xylem tissue via ray cells that redistributes elements in other portions of wood (Watmough 1999;Bilodeau-Gathier et al 2008). Elements are potentially mobile within the xylem long after their uptake, and the mobility of water-soluble base cations (Ca, Mg, and K) increases at higher soil acidity (Bilodeau-Gauthier et al 2011). McClenahen et al (1989 reported Mn and Ca elements that are likely to move laterally.…”
Section: Discussionmentioning
confidence: 99%
“…Any change in organic or inorganic ligands will alter metal speciation in soil and, in turn, the mobility and bioavailability (Bilodeau-Gauthier et al, 2011). EDTA is most effective under acidic and neutral conditions whereas its metal binding efficiency decreases with increase in pH.…”
Section: Effect Of Ph On Organic Ligands-induced Variation In Pb Specmentioning
confidence: 99%
“…1998;St. Clair et al, 2005;Schaberg et al, 2006;Bilodeau-Gauthier et al, 2011;and others). Mean foliar nutrient values for N, S, P, Ca, and Mg in stands with and without dieback were lower than baseline foliar values determined in similar plot locations in eastern Minnesota and northern Michigan in 1993 (Burton et al, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…Clair et al, 1995;Hallett et al, 2006;Schaberg et al, 2006;Houle et al, 2007;Long et al, 2009), usually Ca, Mg, Mn, Al, P, K, and N. Some of the more recent reports have been including other micronutrient correlations as well (Heisey 1995;St. Clair and Lynch, 2005;Watmough, 2010;Bilodeau-Gauthier et al, 2011 equations have been published for sugar maple nutrition based on some extant datasets and may be useful for diagnosing and prescribing fertilizer (Lozano and Huynh, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation